2012
DOI: 10.1021/om3010806
|View full text |Cite
|
Sign up to set email alerts
|

Diamine Bis(phenolate) as Supporting Ligands in Organoactinide(IV) Chemistry. Synthesis, Structural Characterization, and Reactivity of Stable Dialkyl Derivatives

Abstract: The homoleptic compounds [U(salan-R2)2] (R = Me (1), tBu (2)) were prepared in high yield by salt-metathesis reactions between UI4(L)2 (L = Et2O, PhCN) and 2 equiv of [K2(salan-R2)] in THF. In contrast, the reaction of the tetradentate ligands salan-R2 with UI3(THF)4 leads to disproportionation of the metal and to mixtures of U(IV) [U(salan-R2)2] and [U(salan-R2)I2] complexes, depending on the ligand to M ratio. The reaction of K2salan-Me2 ligand with U(IV) iodide and chloride salts always leads to mixtures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 90 publications
(169 reference statements)
5
29
0
Order By: Relevance
“…[2][3][4][5] It was envisaged that the mixedsandwich ligand system consisting of dianionic COT TIPS2 (where COT TIPS2 = 1,4-{Si i Pr 3 } 2 C 8 H 6 ) and monoanionic Cp* ligands may provide sufficient steric and electronic stabilisation to isolate a Th(III) compound, which would be expected to display high reactivity towards CO or CO 2 in a manner similar to the analogous trivalent uranium system U(COT TIPS2 )-Cp*. 8 Subsequently, a number of Th(IV) alkyl complexes have been synthesised, both in metallocene [9][10][11][12][13][14][15][16] and non-metallocene [17][18][19][20] ligand frameworks, and a small number of these have shown insertion reactivity towards CO 2 . In addition to the reduction chemistry, the reactivity of Th-C and Th-H bonds in thorium(IV) systems towards small molecules such as CO 2 is also of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] It was envisaged that the mixedsandwich ligand system consisting of dianionic COT TIPS2 (where COT TIPS2 = 1,4-{Si i Pr 3 } 2 C 8 H 6 ) and monoanionic Cp* ligands may provide sufficient steric and electronic stabilisation to isolate a Th(III) compound, which would be expected to display high reactivity towards CO or CO 2 in a manner similar to the analogous trivalent uranium system U(COT TIPS2 )-Cp*. 8 Subsequently, a number of Th(IV) alkyl complexes have been synthesised, both in metallocene [9][10][11][12][13][14][15][16] and non-metallocene [17][18][19][20] ligand frameworks, and a small number of these have shown insertion reactivity towards CO 2 . In addition to the reduction chemistry, the reactivity of Th-C and Th-H bonds in thorium(IV) systems towards small molecules such as CO 2 is also of interest.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Alternatively, the in situ reduction of a mixed sandwich Th(IV) halide precursor in the presence of a small molecule may produce a transient Th(III) intermediate, which could induce reductive transformations. [20][21][22] Th(IV) hydride complexes have also been synthesised, mainly supported by cyclopentadienyl-based ligands, and containing both bridging and terminal hydride ligands, however their CO 2 insertion chemistry has not been extensively explored. This was first reported by Marks and Moloy in 1985, who demonstrated the ability of Th(Cp*) 2 (Me) 2 to insert 2 equivalents of CO 2 to form a bis-acetate, Th(Cp*) 2 (OAc) 2 , and that Th(Cp*) 2 (OCH t Bu 2 )(H) will insert 1 equivalent of CO 2 to yield a formate complex, Th(Cp*) 2 (OCH t Bu 2 )(κ 2 -O 2 CH).…”
Section: Introductionmentioning
confidence: 99%
“…The six-coordinated alkyl complexes Th(salan-t Bu 2 )(CH 2 SiMe 3 ) 2 and U(salan-t Bu 2 )(CH 2 SiMe 3 ) 2 were prepared according to Scheme 181 by addition of LiCH 2 SiMe 3 to the chloride precursor in toluene, and their solution (for Th(salan-t Bu 2 )(CH 2 SiMe 3 ) 2 ) and solid-state structures were determined by NMR and X-ray studies. These complexes were found to be stable for days at room temperature [154].…”
Section: Organolanthanides In Materials Sciencementioning
confidence: 97%
“…In the presence of traces of LiCl, crystals of the dimeric insertion product Th 2 Cl(salan-t Bu 2 ) 2 (-1 : 1 -O 2 CCH 2 SiMe 3 ) 2 (-1 : 2 -O 2 CCH 2 SiMe 3 ) were isolated (Scheme 182). The structure showed that CO 2 insertion occurs in both alkyl groups and that the resulting carboxylate is easily displaced by a chloride anion (via intermediates A and B) [154]. Uranium(IV) alkyl complexes of a rigid dianionic NONdonor ligand have been studied in detail.…”
Section: Organolanthanides In Materials Sciencementioning
confidence: 99%
“…Salans are sequential tetradentate‐dianionic {ONNO}‐type ligands that include sp 3 N‐donors and two phenolate arms connected to the N‐donors via methylene bridges With a typical two‐carbon bridge between the N‐donors, salans bind to metals forming a 6–5–6 tri‐chelate array. Complexes of salans around various transition and main‐group metals of various coordination numbers have been described in the past two decades, and have been employed as catalysts in different transformations including the stereoselective polymerization of alpha‐olefins, and the asymmetric oxidation of sulfides and olefins . The sequential nature of the salans, combined with the flexibility around the N‐donors, may lead to several modes of wrapping of the salans around the metal centers, and consequently to stereoisomer mixtures.…”
Section: Introductionmentioning
confidence: 99%